Otomycosis: A Comprehensive Review - Priyanka Debta1, Santosh Kumar Swain2, Smarita Lenka3, Mahesh Chandra Sahu4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
When the external auditory canal is infected with an isolated fungal infection, it is called Otomycosis. Itseems to be a very common clinical condition found in the outpatient department of otorhinolaryngology allover the world. The etiological microorganisms that form biofilm inside the earcanal are mostly Aspergillusand Candida species. Improper self-cleaning,self-medication, and insert of unnecessary tools into the earcanal can lead to the onset of otomycosis. The major symptoms of otomycosis are earache,ear discharge, andhearing loss. So the right diagnosis is a must to take a percussive step during the primary stage of infection.But when infection is spread up to a mastoid area with suppurative condition then it needs special medicalattention especially in patients with low immunity. This comprehensive review has the aim to bringattentionto self-hygiene and proper health education to maintain a healthy life